(untitled) (SCIENCE TIME JOURNAL, 2026)
The rapid development of artificial intelligence (AI) technologies has considerably transformed contemporary educational practices, particularly in the field of academic writing instruction. This study investigates the impact of AI-based feedback tools on the academic writing performance of English as a Foreign Language (EFL) students. Special attention is given to the pedagogical role of platforms such as ChatGPT, Grammarly, and QuillBot in improving grammatical accuracy, lexical richness, coherence, academic style, and overall writing quality. The research employed both qualitative and quantitative approaches involving experimental and control groups of university students. Data were collected through pre-tests, post-tests, classroom observations, questionnaires, and comparative writing assessments. The findings demonstrate that students who utilized AI-assisted feedback systems showed significantly higher improvement in academic writing performance compared to those using traditional feedback methods. In particular, AI technologies contributed to faster error correction, increased learner autonomy, enhanced writing fluency, and greater confidence during academic writing tasks. However, the study also identifies several challenges associated with excessive dependence on AI-generated content, including risks related to academic integrity, plagiarism, and reduced independent critical thinking. The article concludes that AI-based feedback tools can serve as highly effective supplementary resources in academic writing instruction when applied under appropriate pedagogical supervision and ethical guidelines.